Proletcultismul (I) - Dumitru Micu (Revista de Istorie și Teorie Literară)
Considering the implications of ”proletcultist” (the cult of proletarian values) literature, we can notice that proletcultism has in common with the vanguard currents the programmatic request of destroying libraries, museums and universities. That is everything related to academic tradition. But, nonetheless, there is a difference between the Romanian ”proletcultism” and the Soviet one. Communism in Russia was more aesthetic-infused, being accepted non-proletarian inspiration also.